STABILISASI TANAH LEMPUNG DENGAN MENAMBAHKAN SERBUK KAYU TERHADAP TINGKAT KEPADATAN TANAH DI DUSUN LANANG - Moh. Nasril; Ilmuddin, Ilmuddin (Jurnal Cakrawala Ilmiah, 2025)
In civil construction, soil plays a crucial role. It must be capable of bearing the entire structural load to prevent failure or damage to the construction. Visually, Dusun Lanang in Lampasio Village is one of the areas characterized by clay-type soil. The main issue with this soil is that it becomes extremely hard during the dry season and excessively soft during the rainy season, making roads and ground surfaces easily damaged. Therefore, stabilization of the soil is necessary. Soil stabilization, in principle, aims to improve the quality of substandard soils. According to Bowles (1984), if the soil in the field is very loose or highly compressible, or if it has an inappropriate consistency index, excessively high permeability, or other undesirable properties that render it unsuitable for a construction project, then stabilization is required. In this study, the author used Sawdust as a stabilizing agent for clay soil, with additive variations of 5%, 10%, and 15%. Based on data analysis obtained from tests conducted at the Laboratory of the Public Works Department of Tolitoli Regency, it can be concluded that the clay soil in Dusun Lanang, Lampasio Village, Lampasio District, is of medium to high plasticity and is considered poor as a subgrade material. The addition of Sawdust to the clay soil significantly improved the California Bearing Ratio (CBR) value. The original soil density was recorded at 0.39%. With the addition of 5% Sawdust, the density increased to 2.09%. A 10% addition resulted in a density of 2.19%, while a 15% addition achieved a density of 4.70%.